Espaços pluriativos da agricultura familiar em Domingos Martins-ES - Guaitolini, Renata Nunes (2015)
The pluriactive spaces of family farming are characterized as farms belonging to farmers which are developed both in agricultural activities and non-agricultural activities, sometimes encouraged by public policies. For better understanding of these spaces and the relevant aspects of your training, such as cultural, spatial, economic and political, was sought through a case study to understand the specifics that led to the formation of pluriactive spaces of family farming in Domingos Martins (ES) - the choice of this city is due both the importance and the amount of existing establishments of family farming in its territory, in addition to the growth of non-agricultural activities within the farms, especially activities related to agroturism. We realize - through the analysis of establishments belonging to the Rural's Circuits tourism of Domingos Martins - the relationship between pluriactive spaces of family farming and rural tourism, agro-tourism and / or ecotourism. Therefore, we identified tourism as a catalyst for public policy and understand that through him the family farms are built and / or processed to meet a tourist demand, which manifests from the introduction of pluriactive practices within those spaces.